When both speed and accuracy are important: using canonical correlation to evaluate skills - Parrington, L.; Ball, K.; MacMahon, C. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Many sports skills such as the tennis serve, goal shot in soccer and golf drive, require both speed and accuracy. However, evaluation of these skills has been limited to assessing these factors separately. The use of analyses that allow for the inclusion of both features is an important direction for sports biomechanics. This study highlights the use of canonical correlation to achieve this. Canonical correlation analysis allows the assessment of relationships between two sets of variables, providing the opportunity for more than one dependent variable. Using Australian football handballing, in which both speed and accuracy are necessary, canonical correlation analysis found a strong relationship between covariate and criterion groups. Moreover, the results differed from the evaluation of speed and accuracy when these had been analysed separately.